A spatial analysis of the achievements, in terms of regional development, accomplished by the initial EU-member cohesion fund beneficiaries using a synthetic indicator - Rodríguez Martín, José Antonio; Martín Martín, José María; Salinas Fernández, José Antonio; Zermeno Mejia, Karla Aida; Ananos Bedrinana, Karen G. (Sustainability, 2019)
This study proposes construction of a synthetic indicator to measure progress toward the objective of economic and social cohesion among the regions of Spain, Greece, Ireland and Portugal within the framework of European Community Regional Policy and the spatial disparities among these countries. Our aim is to integrate, in a single indicator, a large number of variables defined by the European Commission to monitor improvements in regional development, classified according to the objectives of the Europe 2020 Strategy to promote smart, sustainable and inclusive growth. To achieve this goal, we use the Pena distance method for the year 2013.
Keywords: spatial disparities; economic and social cohesion; economic development; European Union; Lisbon strategy; regional policy; synthetic indicator; JCR; Scopus